2020
DOI: 10.48550/arxiv.2008.04374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can We Spot the "Fake News" Before It Was Even Written?

Abstract: Given the recent proliferation of disinformation online, there has been also growing research interest in automatically debunking rumors, false claims, and "fake news." A number of fact-checking initiatives have been launched so far, both manual and automatic, but the whole enterprise remains in a state of crisis: by the time a claim is finally factchecked, it could have reached millions of users, and the harm caused could hardly be undone. An arguably more promising direction is to focus on fact-checking enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Hence, there is still no agreed definition of the term "fake news." Moreover, we can find many terms and concepts in the literature that refer to fake news Molina et al 2021) (Abu Arqoub et al 2022Allen et al 2020;Allcott and Gentzkow 2017;Shu et al 2017;Sharma et al 2019;Zhou and Zafarani 2020;Zhang and Ghorbani 2020;Conroy et al 2015;Celliers and Hattingh 2020;Nakov 2020;Shu et al 2020c;Jin et al 2016;Rubin et al 2016;Balmas 2014;Brewer et al 2013;Egelhofer and Lecheler 2019;Mustafaraj and Metaxas 2017;Klein and Wueller 2017;Potthast et al 2017;Lazer et al 2018;Weiss et al 2020;Tandoc Jr et al 2021;Guadagno and Guttieri 2021), disinformation (Kapantai et al 2021;Shu et al 2020a, c;Kumar et al 2016;Bhattacharjee et al 2020;Marsden et al 2020;Jungherr and Schroeder 2021;Starbird et al 2019;Ireton and Posetti 2018), misinformation (Wu et al 2019;Shu et al 2020c;Shao et al 2016Shao et al , 2018bMicallef et al 2020), malinformation (Dame Adjin-Tettey 2022) (Carmi et al 2020;…”
Section: Definitions Of Fake Newsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there is still no agreed definition of the term "fake news." Moreover, we can find many terms and concepts in the literature that refer to fake news Molina et al 2021) (Abu Arqoub et al 2022Allen et al 2020;Allcott and Gentzkow 2017;Shu et al 2017;Sharma et al 2019;Zhou and Zafarani 2020;Zhang and Ghorbani 2020;Conroy et al 2015;Celliers and Hattingh 2020;Nakov 2020;Shu et al 2020c;Jin et al 2016;Rubin et al 2016;Balmas 2014;Brewer et al 2013;Egelhofer and Lecheler 2019;Mustafaraj and Metaxas 2017;Klein and Wueller 2017;Potthast et al 2017;Lazer et al 2018;Weiss et al 2020;Tandoc Jr et al 2021;Guadagno and Guttieri 2021), disinformation (Kapantai et al 2021;Shu et al 2020a, c;Kumar et al 2016;Bhattacharjee et al 2020;Marsden et al 2020;Jungherr and Schroeder 2021;Starbird et al 2019;Ireton and Posetti 2018), misinformation (Wu et al 2019;Shu et al 2020c;Shao et al 2016Shao et al , 2018bMicallef et al 2020), malinformation (Dame Adjin-Tettey 2022) (Carmi et al 2020;…”
Section: Definitions Of Fake Newsmentioning
confidence: 99%
“…There is also a remarkable amount of disagreement over the classification of the term fake news in the research literature, as well as in policy (de Cock Buning 2018;ERGA 2018ERGA , 2021. Some consider fake news as a type of misinformation (Allen et al 2020;Singh et al 2021;Ha et al 2021;Shao et al 2018b;Di Domenico et al 2021;Sharma et al 2019;Celliers and Hattingh 2020;Klein and Wueller 2017;Potthast et al 2017;Islam et al 2020), others consider it as a type of disinformation (de Cock Buning 2018) (Bringula et al 2022;Baptista and Gradim 2022;Tsang 2020;Tandoc Jr et al 2021;Bastick 2021;Khan et al 2019;Shu et al 2017;Nakov 2020;Shu et al 2020c;Egelhofer and Lecheler 2019), while others associate the term with both disinformation and misinformation (Wu et al 2022;Dame Adjin-Tettey 2022;Hameleers et al 2022;Carmi et al 2020;Allcott and Gentzkow 2017;Zhang and Ghorbani 2020;Potthast et al 2017;Weiss et al 2020;Tandoc Jr et al 2021;Guadagno and Guttieri 2021). On the other hand, some prefer to differentiate fake news from both terms (ERGA 2018;Molina et al 2021;ERGA 2021) (Zhou and Zafarani 2020;…”
Section: Definitions Of Fake Newsmentioning
confidence: 99%
“…Several recent works [19], [20] have shown that the credibility or trustworthiness of media outlets can be used as a weak signal to fact-check the news articles that are published by the corresponding media outlets. These works attempt to assign a credibility score for each news outlet based on its previous publications and propagate the same label for future publications coming from the same outlet.…”
Section: Source Credibilitymentioning
confidence: 99%
“…Text content-based approaches [31], [53], [54] explore word usage and linguistic styles in the headline and body of news records to identify fake news. Some works explore the credibility of the source of the articles [17], [19]. Also, some works [6], [9], [37], [38], [55], [56] exploit the features from the social context (e.g., the features of the propagation pattern and the characteristics of the users engaging with the news records) of news records to identify their veracity with the help of machine learning techniques such as Propagation Tree Kernels [56], Recurrent Neural Networks [37], [55], and Graph Neural Networks [9].…”
Section: Multi-modal Fake News Detectionmentioning
confidence: 99%
“…NLP technology could also be leveraged in proactive strategies. Prior work has employed network analysis and similar techniques to identify key actors for intervention in social networks (Farajtabar et al, 2017); using NLP, such techniques could be extended to take into account the information shared by these actors, in addition to graph-based features (Nakov, 2020;Mu and Aletras, 2020). Another direction is to disseminate countermessaging before misinformation can spread widely; this is also known as pre-bunking, and has been shown to be more effective than post-hoc debunking (van der Linden et al, 2017;Roozenbeek et al, 2020;Lewandowsky and van der Linden, 2021).…”
Section: Research Challengesmentioning
confidence: 99%